Implementasi Komite Pengendalian dan Pencegahan Resistensi Antimikroba dalam Perspektif Hukum Kesehatan di RSUD Ulin Banjarmasin: Implementation of The Antimicrobial Stewardship Comittee to Prevent Antibiotic Resistance: A Health Law Perspective at Ulin Hospital Banjarmasin - Pasaribu, Munawaroh; Noor Rahman, Aditya; Insani, Dina Aulia (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
This study emphasizes the relationship between legal aspects and health policy implementation, particularly the Antimicrobial Resistance Control and Prevention Program (PPRA) based on Ministry of Health Regulation No. 8 of 2015 and No. 28 of 2021. The program represents the hospital’s legal responsibility to ensure the right to safe, high-quality, and rational healthcare. Antimicrobial resistance, which increases patient morbidity and mortality, has become a global and national problem. This research employs a juridical-empirical method with a sociological approach, combining primary data from interviews with PPRA administrators and secondary data from legal documents and hospital policies. The results indicate that antibiotic use at Ulin Regional Hospital, Banjarmasin, has been regulated according to the PPRA guidelines established by the hospital director. However, implementation remains suboptimal, particularly in planning, supervision, and healthcare workers’ understanding of rational antibiotic use. The lack of management support and coordination serves as a major obstacle. Strengthening hospital information systems, managerial support, and active involvement of all health professionals are essential to ensure the sustainability of PPRA. From a health law perspective, PPRA implementation at Ulin Hospital has not fully met the principles of legal governance in healthcare. Strengthening internal regulations, enhancing managerial oversight, and conducting periodic evaluations based on the patient safety principle are required to improve compliance and service quality.